3-Iodo-2,6-dinitrotoluene - Watkin, D; Motherwell, W; Cooper, R; Pantos, S; Steadman, O (2005)
The structure of the title compound, C7H5IN 2O4, was determined as one of a group of five related compounds, in order to assess its suitability as a test material for the 2004 Cambridge Crystallographic Data Centre 'Blind Structure Prediction Test'. The crystal structure consists of columns of nearly planar molecules stacked parallel to the a axis, with an interplanar spacing of 3.478 (3) Å. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.